PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN DAMPAK PANDEMI COVID-19 TERHADAP MANAJEMEN LABA - Indah Nur Rohmatika (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to determine and examine the effect of good corporate governance mechanisms (audit committee, independent board of commissioners, managerial ownership, institutional ownership), leverage, and the impact of the covid-19 pandemic on earnings management in manufacturing companies in a row in 2017-2020. This study uses a quantitative approach with secondary data derived from annual reports and company financial statements. The research sample was taken by purposive sampling method with the number of samples according to the criteria of 40 companies. The analytical technique method used is multiple linear regression analysis. The results showed that the independent audit committee and board of commissioners had a significant negative effect on earnings management. Meanwhile, leverage has a significant positive effect on earnings management. Managerial ownership, institutional ownership, and the impact of the COVID-19 pandemic have no effect on earnings management.